Peroxisome proliferator-activated receptor gamma (PPARγ) in brown trout: Interference of estrogenic and androgenic inputs in primary hepatocytes - Lopes C. (2016)
Peroxisome proliferator-activated receptor gamma (PPARγ) is a pivotal regulator of lipid and glucose metabolism in vertebrates. Here, we isolated and characterized for the first time the PPARγ gene from brown trout (Salmo trutta f. fario). Hormones have been reported to interfere with the regulatory function of PPARγ in various organisms, albeit with little focus on fish. Thus, primary hepatocytes isolated from juveniles of brown trout were exposed to 1, 10 and 50 μM of ethinylestradiol (EE2) or testosterone (T). A significant (3 fold) decrease was obtained in response to 50 μM of EE2 and to 10 and 50 μM of T (13 and 14 folds), while a 3 fold increase was observed at 1 μM of EE2. Therefore, trout PPARγ seems a target for natural/synthetic compounds with estrogenic or androgenic properties and so, we advocate considering PPARγ as another alert sensor gene when assessing the effects of sex-steroid endocrine disruptors. © 2016 Elsevier